Convergent by formation: the new paradigm and the challenges for future professional generations and journalism courses | DOI: 10.21204/2359-375X/ancora.v3n1p100-124 - BECKER, Maria Lúcia (2016)
The article proposes a reflection on convergence journalism and on thelearning process that may enable new generations to practice the type of professional exercise that is demanded in the labor market. Based on a bibliographical research and on data derived from the participant observation carried out during the discussions about the new Pedagogical Project of the UEPG’s Journalism Course, this study produces a historical and theoretical systematization of convergence – of media, of cultural industries’ products and of information, culture and leisure consumption models. In addition, the article reunites characteristics of the new paradigm in journalism, as well as indicates some of the challenges posed to students, teachers and courses during this process of changes.